ANTIBACTERIAL ASSESSMENT OF ALOE VERA (Aloe vera chinensis Linn) CORTEX EXTRACT AND ITS APPLICATION AS INHIBITOR FOR KING PRAWNS (Macrobrachium rosenbergii Linn) SPOILAGE DURING STORAGE AT 5oC - Muhammad Nur Cahyanto, Sutardi Andri Nofreeana (Proceeding of International Congress, 2014)
Aloe vera (Aloe vera chinensis Linn) cortex contains antibacterial compounds such as aloe emodin andaloin, that have potency as natural preservative for foods. The objectives of the research were to determinethe minimum concentration of aloe vera cortex extract to inhibit bacterial growth, and the effects of soakingin the extract and storage at 5oC on the quality parameters of king prawns. The concentrations of extractwere varied i.e. 125, 250, 500 and 1000 Î¼g/ml, respectively, and minimum concentration of extract forinhibition of Pseudomonas fluorescens was determined by Minimum Inhibitory Concentration (MIC)method. Antibacterial compounds in the extract were analyzed by HPLC and TLC methods. TPC, TVBâN,TMA, pH and organoleptic characteristics of soaked king prawns were evaluated. The results showed 500Î¼g/ml aloe vera cortex extract was an optimum concentration, and soaking for 90 minutes was able toinhibit and to reduce one log cycle of bacteria population. Aloe vera cortex extracts contained 18.21 ppmaloe emodin and 15.5 mg/g aloin (1.55%). After 6 days storage at 5oC, therefore the king prawns was performedby TPC 3.9 x 105, TVBâN 28,6, TMA 4.60 and pH 7.7. The best quality of king prawns was resultedby 60 minutes soaking with organoleptic score 7.Keywords: Aloe vera; antibacterial; aloe emodin; aloin; king prawns.